2010
DOI: 10.3390/molecules15031223
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antiradical Activity of Schisandra Chinensis Lignans Using Different Experimental Models

Abstract: The in vitro antiradical activity of Schisandra chinensis lignans was investigated using DPPH, ABTS+, Fenton reaction inhibition and tyrosine-nitration inhibition assays, as were the in vivo antidiabetic activities of selected lignans in an animal model of alloxan-induced diabetes. Different degrees of antiradical activity were found, depending upon the structural parameters of the tested compounds. Unfortunately, the compounds showed no antidiabetic activity in concentration range tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The colorful skins derived from anthocyanin also attract animals to eat the fruits and thereby disperse the seeds. 4 Many studies have shown that the major bioactive components of S. chinensis fruits are essential oil 5 and biphenyl cyclooctene lignans; 6,7 the pharmacological activity is significant, and includes antibacterial, antioxidant, cytotoxic, cancer chemopreventive 8,9 and anti-HIV-1 activity. 10 At present, studies of the active components and pharmacology of schisandra fruits mainly focus on lignans.…”
Section: Introductionmentioning
confidence: 99%
“…The colorful skins derived from anthocyanin also attract animals to eat the fruits and thereby disperse the seeds. 4 Many studies have shown that the major bioactive components of S. chinensis fruits are essential oil 5 and biphenyl cyclooctene lignans; 6,7 the pharmacological activity is significant, and includes antibacterial, antioxidant, cytotoxic, cancer chemopreventive 8,9 and anti-HIV-1 activity. 10 At present, studies of the active components and pharmacology of schisandra fruits mainly focus on lignans.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Some recent experiments proved that these data showed only the low activity of lignans in assays using synthetic radicals. [18] Only schisandrin (4) and -schisandrin (5) were active in our study. The ability of schisandrin (4) and -schisandrin (5) to reduce the NO production in the cell tissue after LPS stimulation agrees with a previous report of Opletal and Opletalová, who described that an alcoholic extract from S. chinensis fruits containing dibenzocyclooctadiene lignans inhibit the quantity of NO in saliva obtained from sportsmen undergoing physical stress.…”
Section: Resultsmentioning
confidence: 89%
“…and M. pomifera (pomiferin (1), osajin (2)), as previously described [ Figure 1], [11,18,19] in purity >95% (HPLCverifi ed), were dissolved in 40% DMSO with 10% 0.1 M NaOH and stock solutions of concentrations 0.25, 2.5, 25, 50, 125 and 250 μM were prepared. In our experiments, the fi nal concentration of DMSO in cell culture never exceeded 0.4%, which did not affect the viability of the cells.…”
Section: Preparation Of the Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Provious studies had proved that schisandra lignans derivatives were useful in protecting liver from free radical attack (Ip et al, 1996). The lignans are good antioxidants both in vitro and in vivo (Choi et al, 2006;Smejkal et al, 2010). Our previous studies suggested a correlation between immunocompetence and antioxidative capacity in immunocytes (He et al, 2009b).…”
Section: Notementioning
confidence: 97%